الشبكات الدلالية العربية ودورها في إثراء المحتوى العربي على الإنترنت - فرج، حنان أحمد إبراهيم (جامعة بني سويف - كلية الآداب, 2020)
تهدف الدراسة إلى إعطاء صورة لواقع الشبكات العربية الدلالية ودورها في إثراء المحتوى العربي على الإنترنت كما تهدف إلى التعريف بمفهوم الأنطولوجيا وعلاقتها بالويب الدلالي، كما ناقشت الدراسة الدوافع لبناء شبكات عربية دلالية والصعوبات التي تواجه بناء تلك الشبكات الدلالية مع شرح لواقع الشبكات الدلالية العربية والتعريف بنموذجين من الشبكات الدلالية العربية (Arabic WorldNet -Arabic Ontology ).وأسفرت الدراسة على أن هناك ضعف شديد في بناء أنطولوجيا باللغة العربية، وتواجه بناء أنطولوجيا اللغة العربية تحديات نظرا لصعوبة بنائها والاتفاق على مكوناتها.
The aim of this study to give a picture of the reality of the Arab semantic networks and their role in enriching the Arabic content on the Internet. It also aims to introduce the concept of ontology and its relation to the semantic web. The study also discussed the motives for building Arab networks, the difficulties encountered in constructing these semantic networks, explaining the reality of semantic networks. The study revealed that there is a serious weakness in building the Arabic language ontology, and the construction of the Arabic language ontology is facing challenges to the difficulty of building it and agreeing on its components.
Keywords: المواقع الإلكترونية -- الويب الدلالي -- خدمات المعلومات -- الوطن العربي